Forecasting the development of acute kidney injury using a recurrent neural network - Kallenberger, Stefan M.; Schmidt, Constanze (Cardiovascular research, 2019)
Commentary on ‘A clinically applicable approach to continuous prediction of future acute kidney injury’, by N. Tomašev et al., Nature, 2019.
Gesehen am 08.06.2020